Indonesian Migrant Workers: The Analysis of Legal Policy in Gender Issue - Bahir Mukhammad; Sri Wahyu Kridasakti; Paulus Rudolf; Umu Hilmy (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
The majority of Indonesian migrant workers (PMI) are women (85%), who frequently face gender-based rights violations and inadequate legal protection abroad. While the Declaration of Human Rights promotes equality, these principles often remain nominal, with basic human rights (Law No. 39/1999) being overlooked by host country authorities. Legal issues faced by female PMI stem largely from limited legal literacy regarding both Indonesian and host country labor laws. From a legal-historical perspective, gender-related socio-legal constructions have perpetuated an unequal division of roles for women. This study addresses the historical legal regulation of Indonesian migrant workers from a gender perspective in host countries. The study aims to offer policy insights for curriculum development in PMI training and promote legal literacy through MOOCs. Using a normative legal-historical approach and statute-based analysis, this research examines labor laws from four host countries (Saudi Arabia, Hong Kong, Malaysia, and Taiwan), supported by secondary sources such as academic texts and media reports. All materials are analyzed using an interactive qualitative data model and the analytical theory of legal protection. The results show gaps in laws for protecting workers, mainly due to limited regulations and legal knowledge. While national efforts such as Law No. 18 of 2017 and the establishment of BNP2TKI (via Presidential Regulation No. 81/2006) represent progress, further improvement is needed.  Hence, the study suggests adding gender-sensitive legal topics into PMI training and using MOOCs to increase legal awareness for female migrant workers.